Cross-Space Risk Assessment of Cyber-Physical Distribution System Under Integrated Attack - Jie Yang (IEEE, 2021)
Assessing cross-space risk of cyber-physical distribution system under integrated attack is investigated in this paper. Firstly, a hierarchical structure of cyber-physical distribution network according to IEC 61850 is established and a deliberate attack scenario with limited adversarial knowledge and stealth requirement is developed based on a general linear model for state estimation. Then, we formulate two optimization problems to describe the attack implementation and propagation process and obtain the likelihood of attacks including a robust solution and a risk solution in a fuzzy Bayesian network (BN). On this basis, a physical impact metric is defined as the integrated deviation of system states and measurements. Thus, the cross-space risk assessment can be performed. Finally, the simulation results of case studies demonstrate that the proposed method is effective and provides a broad and clear view of cyber-physical distribution system security situation.